Assessing the Effect of Fe2O3 Nanoparticles on Catalase Activity in Patients with Chronic Periodontitis: In Vitro study and Molecular Docking - Hatem, Sara A.; Nasif, Zaizafon N.; Al-Rubaee, Eaman A. S. (Iraqi Journal of Science, 2024)
Periodontal disease, also known as gum disease, is a chronic inflammatory condition that affects the supporting structures of the teeth, including the gums and underlying bone. It is primarily caused by a bacterial infection resulting from poor oral hygiene practices. The main objectives of the current study were to synthesize iron oxide nanoparticles (Fe2O3-NPs) and their characteristics were analyzed through UV, SEM, and X-ray analysis. Additionally, the dispersion of the synthesized NPs was investigated using UV and TEM techniques. The study also aimed to assess the kinetic behavior and the impact of Fe2O3-NPs on catalase activity in the saliva of the patient and control groups. The findings revealed a significant increase in catalase activity (p>0.05) in both serum and saliva of all patient groups compared to the control group. The UV-visible spectrum shows that the absorption peaks for synthesized α- and γ-iron oxide nanoparticles was at 225 nm. According to the SEM image analysis, the primary particle size of the nano-particles is approximately 26.8 nm. The X-ray diffraction results indicate that the Fe2O3-NPs range in size from 14 nm to 26 nm. UV and TEM study conclude that water a suitable solvent for Fe2O3-NPs dispersion on kinetic study of catalase (CAT) activity. The kinetic data cleared that the α-Fe2O3-NPs have an inhibitory effect for the total activity of salivary CAT in the samples of both healthy and patients with chronic periodontitis. Lineweaver–Burk graph showed that (α-Fe2O3) inhibit catalase by un comp. inhibition. γ-Fe2O3-NPs inhibited total salivary CAT activity in healthy and patients with chronic periodontitis samples. Lineweaver –Burk graph showed that (γ-Fe2O3) inhibit catalase by uncompetitive inhibition.